2021
DOI: 10.1016/j.cjtee.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical and paraclinical findings have the power to predict critical conditions of injured patients after traumatic injury resuscitation? Using data mining artificial intelligence

Abstract: Purpose The triage and initial care of injured patients and a subsequent right level of care is paramount for an overall outcome after traumatic injury. Early recognition of patients is an important case of such decision-making with risk of worse prognosis. This article is to answer if clinical and paraclinical signs can predict the critical conditions of injured patients after traumatic injury resuscitation. Methods The study included 1107 trauma patients, 16 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…For this purpose, paraclinical and clinical data were extracted. Diastolic blood pressure, GCS, and BE after resuscitation crystallized as the most impactful parameters; the outcome was predicted with high accuracy of 0.99 ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, paraclinical and clinical data were extracted. Diastolic blood pressure, GCS, and BE after resuscitation crystallized as the most impactful parameters; the outcome was predicted with high accuracy of 0.99 ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of imputation methods, mean imputation was the most used among the 33 studies which mention how the missing values were handled. Other imputation methods used were iterative or multiple imputation, ElasticNet regression, optimal imputation, chained equation imputation, and median imputation [ 30 , 35 , 44 , 62 , 70 , 71 , 80 , 94 , 97 , 110 , 113 ]. For dealing with imbalanced data, 6 studies addressed it with the most commonly used method being Synthetic Minority Over-Sampling Technique [ 49 , 63 , 72 , 81 , 91 , 99 ].…”
Section: Application Of ML Algorithms For Hemorrhagic Traumamentioning
confidence: 99%
“…Kilic et al [ 28 ] and Pearl et al [ 78 ] found that physiological variables from the scene had little to no impact on the performance of their model; Kilic also noted that response to resuscitation had an important effect on trauma mortality [ 28 , 78 ]. Paydar et al [ 97 ] reported that DBP was more important than SBP as a predictor for mortality, while Walczak et al [ 103 ] found that SBP was the second most contributing variable for transfusion prediction.…”
Section: Application Of ML Algorithms For Hemorrhagic Traumamentioning
confidence: 99%
“…Previous studies have applied PCA to detect patterns reflecting dysregulation of the coagulation system using laboratory parameters 8–10 and to predict early organ dysfunction in trauma patients using circulating inflammatory mediators 11 . In addition, there has been a recent push to apply data-driven computational methods to complex problems like trauma triage 12 . However, to our knowledge, the use of PCA as a predictive tool in pediatric trauma has not yet been investigated.…”
mentioning
confidence: 99%